The Contribution of the International Organization of Francophonie in Cultural Matter in the Republic of Congo from 1981 to 2016 - Hortense Kouya Kouya; Dominique Oba (RIRAI Publisher, 2021)
Colonization has had a lasting impact on African life. This movement instilled a new culture within these colonies. Among these African countries is the Congo. On the whole, these countries have experienced some disputes near where it was a question of meeting around an international body which is none other than the Francophonie for the countries or states colonized by France. It is in this sense that under the leadership of three African Heads of State,Léopold Sédar Senghor from Senegal, Habib Bourguiba from Tunisia and Hamani Diori from Niger, and of Prince Norodom Sihanouk of Cambodia, the representatives of 21 states and governments signed in Niamey, on March 20, 1970, the convention establishing the Agency for Cultural and Technical Cooperation (ACCT). New intergovernmental organization based on the sharing of a common language, French. The Congo being colonized by France adheres to the International Organization of Francophonie on December 7 to 9, 1981, during the general conference held in Libreville, Gabon. And the Congolese government has come to understand that ensuring a better vision on culture and politics can lead the Congo to sustainable development. Hence the need for the Congolese state to cooperate with the International Organization of Francophonie for better visibility for the cultural and political promotion of the country. This is what the subject of our study is: the contribution of the OIF in cultural and political matters in the Republic of Congo from 1981 to 2016.